(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In the interview we sought to understand the scenotechnical craft in its relationship with the spaces and means of work; in the case of Aníbal Marques, this meeting promotes a particular view of the scenic work in the relationship between his craft and his main workspace - the Theatro Municipal de São Paulo (TMSP), where he has been head of the scenotechnic team since 1992. The interview composes a set of records of memories collected during the development of the master’s research Cenotecnia, a criação dos os operários da cena: Um estudo sobre as funções dos trabalhadores cenotécnicos da cidade de São Paulo developed within the scope of NETOC/GPHPC and defended at PPGAC/UFSJ.